2022
DOI: 10.1111/ele.14118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat destruction on coevolving metacommunities

Abstract: Habitat destruction is a growing threat to biodiversity and ecosystem services. The ecological consequences of habitat loss and fragmentation involve reductions in species abundance and even the extinction of species and their interactions. However, we do not yet understand how habitat loss alters the coevolutionary trajectories of the remaining species or how coevolution, in turn, affects their response to habitat loss. To investigate this, we develop a spatially explicit model which couples metacommunity and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…For restoration efficiency of regional interaction abundance, we used linear mixed models in the lme4 package in R. We chose metanetwork structure, metanetwork size, interaction extinction threshold (fraction of habitat loss at which that interaction becomes globally extinct), and interaction degree (sum of degrees of the two species involved in the interaction, Gawecka et al, 2022) as the fixed effects, and metanetwork ID as the random effect. We fitted these models for each restoration simulation (i.e., restoration starting at different fractions of habitat loss), scaling the explanatory variables such that their slope parameter estimates are comparable for a given restoration simulation (Schielzeth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For restoration efficiency of regional interaction abundance, we used linear mixed models in the lme4 package in R. We chose metanetwork structure, metanetwork size, interaction extinction threshold (fraction of habitat loss at which that interaction becomes globally extinct), and interaction degree (sum of degrees of the two species involved in the interaction, Gawecka et al, 2022) as the fixed effects, and metanetwork ID as the random effect. We fitted these models for each restoration simulation (i.e., restoration starting at different fractions of habitat loss), scaling the explanatory variables such that their slope parameter estimates are comparable for a given restoration simulation (Schielzeth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We then investigated which properties of the metanetwork or the interaction affect the restoration efficiency, R. For the network level restoration efficiency measures (local interaction richness and network similarity), we used linear models with metanetwork structure (PC1) and metanetwork size (total number of species in the metanetwork) as the explanatory variables. For restoration efficiency of regional interaction abundance, we used linear mixed models in the lme4 package in R. We chose metanetwork structure, metanetwork size, interaction extinction threshold (fraction of habitat loss at which that interaction becomes globally extinct) and interaction degree (sum of degrees of the two species involved in the interaction, Gawecka et al, 2022) as the fixed effects, and metanetwork ID as the random effect. We fitted these models for each restoration simulation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…5, row 2). Evolutionary responses to HL and fragmentation have been studied theoretically, for example for evolution of dispersal distance (North et al, 2011) and coevolution of interacting species (Gawecka et al, 2022), as well as observed empirically. For example, selection of better colonization ability was observed in a large butterfly metapopulation in Finland (Fountain et al, 2016).…”
Section: Effects Of Eco-evolutionary Dynamicsmentioning
confidence: 99%
“…Furthermore, when the trait variation is heritable, it can also help mitigate the effects of environmental change through "evolutionary rescue" (Bell & Gonzalez, 2011;Boeye et al, 2013;Gonzalez et al, 2013), or conversely aggravate the negative effects through "evolutionary trapping" (Ferriere & Legendre, 2013). These reciprocal effects can lead to eco-evolutionary feedbacks, between the population dynamic consequences of HL and trait variation, which are increasingly being recognised (Legrand et al, 2017;Faillace et al, 2021;Gawecka et al, 2022).…”
Section: Introductionmentioning
confidence: 99%